Systematic Literature Review: Greenwashing and its Impacts on Sustainability and Corporate Practices - Aji, Dinar Yoga Baskoro; Adiwijaya, Zainal Alim (Jurnal Bisnis Mahasiswa, 2025)
This systematic literature review aims to analyze 16 academic articles that discuss the phenomenon of greenwashing, specifically its mechanisms, impacts, and mitigation strategies. The study uses a systematic literature review method based on the Published or Perish application tool. The results show that greenwashing, although often a short-term financial performance enhancer, can undermine long-term stakeholder trust and environmental goals. Key themes found include the role of corporate governance, stakeholder legitimacy, and regulatory intervention in moderating greenwashing. Emerging technologies such as blockchain and green finance are also discussed as mechanisms to counter deceptive environmental claims. The review highlights the persistent challenges of greenwashing in achieving sustainability and proposes an integrated framework for research and policy direction.